A permacultura como estratégia de desenvolvimento local sustentável: o caso do sítio Serra dos Paus Dóias, Exu-Pernambuco - Cabral, Enne Soares (2023)
This research analyzes permaculture via concepts associated with endogenous local economic development by understanding how permaculture moves towards sustainable local economic development; by empirically examining a variety of impacts at a permaculture farm located at Serra dos Paus Dóias in Exu-PE. Concepts were constructed through bibliographical research, and the collection of field research data was carried out at Serra dos Paus Dóias farm in December de 2022. The method selected as best suited this research was the deductive method. The methodological approach adopted for this study relied on both qualitative and quantitative approaches. For the analysis of permaculture technologies, a multidimensional approach was adopted, furthermore, the impacts of each technology/enterprise on the economic, environmental and social dimensions were evaluated. The methodology for the economic dimension was based on the financial viability through the return-on-investment time, on the economic surplus method and on the monetary savings achieved method. With regard to the assessment in the environmental dimension, it identified the improvements resulting from the introduction of the acquired technology. From the point of view of social assessment, similar to the assessment of environmental impacts, the aim was to analyze improvements; in addition to identifying the most relevant components and indicators for assessing the social impacts of technology. Furthermore, when necessary, a comparative method was adopted to enrich the evaluations. It was determined by this study that permaculture evolved towards sustainable local development through the principles of participation of local actors, institutions and government agencies and that the technologies provided a sustainable socioeconomic development for the case of Serra dos Paus Dóias. As such, permaculture was determined to be a viable local development strategy.